2009
DOI: 10.2147/ijwr.s4649
|View full text |Cite
|
Sign up to set email alerts
|

Wine consumers’ environmental knowledge and attitudes: Influence on willingness to purchase

Abstract: The last two decades have witnessed a dramatic increase in environmental consciousness worldwide. Consumers are now changing their behavior to integrate environmental considerations into lifestyle choices. This change includes consumers' purchasing decisions based upon how well products satisfy their needs and how these products affect the natural environment. In some cases, consumers are willing to pay a premium for environmentally friendly products. Marketing professes to serve the benefi t of the public by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(120 citation statements)
references
References 65 publications
9
102
0
9
Order By: Relevance
“…Furthermore, the users' product attitudes were affected by their subjective knowledge. These results were consistent with those reported by Barber et al [19]. Specifically, the higher the consumer awareness of green home appliances, such as knowing that green home appliances with a green mark save energy, the greater their preference for green home appliances will be.…”
Section: Total Effectssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the users' product attitudes were affected by their subjective knowledge. These results were consistent with those reported by Barber et al [19]. Specifically, the higher the consumer awareness of green home appliances, such as knowing that green home appliances with a green mark save energy, the greater their preference for green home appliances will be.…”
Section: Total Effectssupporting
confidence: 92%
“…In the present market, these barriers prevent consumers from understanding how green products affect the environment. More than 80% of Taiwanese people pay additional money to buy products associated with environmental protection, and more than 60% of these consumers pay an additional 10% to purchase green products [19]. In addition, Taiwanese government officials have encouraged people to conserve energy and reduce their carbon dioxide production, promoting political issues regarding standardized energy prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in New World wine-producing countries (South Africa, New Zealand, Australia and USA), there has been an increasing proliferation of wines labelled as sustainable [8,18,21,22]. Many wineries understand that being environmentally friendly has become a strategic business asset for differentiation [23,24].…”
Section: Sustainability Aspects In the Wine Sectormentioning
confidence: 99%
“…In the field of wine, the findings are contradictory. Whilst some authors have shown the influence of the social norm to be one of the most important factors in purchasing decisions (Barber et al, 2009;Barber, 2012), others have reported that the social norm does not influence product acceptance (James & Christodoulidou, 2011;De-Magistris et al, 2015). In light of this background, the following hypothesis was proposed with a view to gaining insight into the contradictory findings of studies on wine: H7.…”
Section: Introductionmentioning
confidence: 99%